Ameliorated in vitro anticancer efficacy of methotrexate d-α-Tocopheryl polyethylene glycol 1000 succinate ester against breast cancer cells - Arehalli S. Manjappa; Popat S. Kumbhar; Rohini Kasabe; Sonali K. Diwate; John I. Disouza (SpringerOpen, 2019)
Abstract Background Methotrexate (MTX), a folate anti-metabolite, has been used widely in the treatment of plenty of malignancies. However, the clinical use is limited because of its poor water solubility (BCS class II drug), nonspecific distribution, drug resistance, short circulation half-life, and toxicity. The objective of the present research was to synthesize the ester prodrug of MTX with d-α-Tocopheryl polyethylene glycol 1000 succinate (TPGS) and characterize for in vitro anticancer efficacy. Results The FTIR and NMR results revealed the successful synthesis of the prodrug. The assay and saturation solubility of the prodrug is found to be 23 ± 2.5% and 6.7 ± 1.3 mg/mL (MTX equivalent) respectively. The CMC of the prodrug in distilled water at room temperature is found to be 36.9 ± 2.6 μg/mL. The prepared prodrug micelles showed a mean particle size of 166 ± 10 nm (PDI, 0.325 ± 0.09). Further, the TEM results confirmed the self-assembling character of the prodrug into micelles with a nearly spherical shape. The prodrug caused the significantly (p < 0.01) less hemolysis (16.8 ± 1.5%) when compared to plain MTX solution and significantly higher (p < 0.01) in vitro cytotoxicity, cell cycle arresting, and apoptosis against human breast cancer cells (MCF-7 and MDA-MB-231). Conclusion Our study results revealed the remarkable in vitro anticancer activity of MTX following its esterification with TPGS. However, further, in vivo studies are needed to prove its efficacy against different cancers.